Arus Utama Wacana Identitas Penghayat Kepercayaan Pasca Putusan MK di Media Daring Kompas.com - Akil Fitra Sholakodin (Faculty of Social Science, Universitas Negeri Malang, 2021)
Reports about believers have drastically increased since the Constitutional Court's Decision Number 97/PUU-XIV/2016 was ratified in 2017. This news is spread in newspapers, television news, and online news articles such as Kompas.com, Suara Merdeka, Detik, and Republika. Reports that contain sensitive issues regarding the formalization of the identity of believers then become public attention. This research is then focused on the discourse that appears in the news on the identity of believers in Kompas.com. The research approach uses qualitative methods with descriptive research types. The data source was taken from a news article from Kompas.com from November 7, 2017, to December 2021. Data analysis was carried out by combining Textual Network Analysis (TNA) and Critical Discourse Analysis (CDA) with the help of NVIVO, WordIJ, and Gephi software. The results of the study show that the formalization of the identity of believers in belief still faces obstacles in the context of discrimination and exclusion that still occur and are carried out by the majority group. Second, the discourse that was developed in the Kompas.com news coverage consisted of five main points that in general encouraged the government's commitment to the implementation of the formalization of the identity of believers. Although in it still raises absolute control of the state related to independence and equality in embracing beliefs and religions.